Study Effect of Performance Wind Turbines on the Performance of DcAc Converter for Dc Motor Application Using Fuzzy Logic Control - suliman, khaled; Ahteewish, Aymen; Baghni, Mohamed (Sharwes Scientific Journal, 2025)
Generation of electricity from wind power has received considerable attention because it is plentiful, renewable, produces no greenhouse gas emissions during operation and uses little land In order to meet the fast dynamic response requirement of the three phase voltage resource rectifier system, this paper designed a voltage fuzzy logic voltage controller with the direct busbar voltage error and the slope of the error based on the theory of fuzzy logic control, and got the parameters of the fuzzy logic controller. A simulation model was created in Matlab. The overshoot of the system response and time of system dynamic response were compared with the experiments of traditional PI controller versus Fuzzy controller based on Matlab-Simulink platform during the operation including starting, increasing load and decreasing load. From the simulation results, this control strategy could improve the dynamic and static performance of the system with the waves of Matlab simulation model, not changing the topology of the system without obviously adding implementation burden of fuzzy controller.